2021
DOI: 10.3390/min11111290
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Concentrations in Roadside Soils on the Białystok-Budzisko Route in Northeastern Poland

Abstract: Civilization development has contributed to environmental pollution. In recent years, the number of vehicles has increased significantly; according to the Central Statistical Office, the number of passenger cars in Poland in 2000 was nearly 10 million, while in 2020 it was slightly more than 25 million. The study aimed to determine the content and spatial distribution of trace elements (Fe, Mn, Cd, Pb, Cr, Ni, Zn and Cu) in the roadside topsoil along the trunk road Białystok–Budzisko on different types of land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…When both factors are prominent, they adversely affect plant physiological and biochemical processes which could lead to growth, biomass, and yield loss [ 4 , 5 ]. Many drought-prone regions such as different parts of China, Africa, Europe, and the Mediterranean shrubland, reported dynamic changes in the metal concentration in soil and its subsequent transfer in plants due to drought stress [ 2 , 6 , 7 , 8 ]. They severely affect seed germination, leaf water content, photosynthetic activity, chlorophyll content, and organelle structure and accelerates senescence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When both factors are prominent, they adversely affect plant physiological and biochemical processes which could lead to growth, biomass, and yield loss [ 4 , 5 ]. Many drought-prone regions such as different parts of China, Africa, Europe, and the Mediterranean shrubland, reported dynamic changes in the metal concentration in soil and its subsequent transfer in plants due to drought stress [ 2 , 6 , 7 , 8 ]. They severely affect seed germination, leaf water content, photosynthetic activity, chlorophyll content, and organelle structure and accelerates senescence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring soil metals result from rock weathering or volcanic eruptions and are less bioavailable compared to sources of anthropogenic origin. Man contributes to high heavy metal soil concentrations through mining, agriculture (fertilization), metallurgy, or fuel combustion and transport [ 4 , 5 ]. Not only do these sources seriously threaten humans, but also animals and plants.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been revealed that the drought can also have various indirect effects on plant growth and development and affects trace elements accumulation, and concentration in soil (Sardans et al 2008). Recent studies regarding droughtprone regions, for example Mediterranean shrubland, different parts of China, Europe and Africa, showed that drought changes the dynamic concentration of elements in soil and accumulation in plants species Peñuelas 2005, 2007;Xia et al 2015;Edokpayi et al 2017;Skorbiłowicz et al 2021). Importantly, drought affects the release of sol-K uble trace elements into the soil solution via the lysis of bacterial cells and the destruction of soil aggregation in drying-rewetting events (Turner and Haygarth 2001).…”
Section: Heavy Metals In the Drought-prone Areasmentioning
confidence: 99%